Changes in the Morphometric Parameters of Large Plain Reservoirs: Causes, Assessments and Consequences (on the Example of the Kama Reservoir) - Aleksandr V. Beloborodov (Водное хозяйство России: проблемы, технологии, управление, 2019)
The paper presents the results of a comparison of the project and refined according to the results of research for 2007–2008 morphometric indicators (area and volume) of the Kama reservoir. Based on a comparison of the design curves and and refined curves of the areas and volumes of the reservoir, as well as diagrams of changes in the total volume of taxons (plots) allocated in the hydrological and morphological zoning, we concluded that the updated data does not correspond to the theoretical ideas about the general orientation of the evolution of the reservoir morphologic parameters. Based on the sedimentation balance data of the Kama reservoir, we have shown that the concept of large-scale changes in the reservoir volume due to the sediment accumulation is untenable. To explain the significant difference between the design and updated data a hypothesis was advanced about incorrect determination of the area and volume of the Kama reservoir in the design studies, due to the low accuracy of cartometric and computational methods in the study of the extremely complex shape of the reservoir bed Similar studies on the Novosibirsk reservoir support these conclusions.